Environment-friendly concrete glue reducing agent and preparation method thereof
By using an environmentally friendly glue reducer containing specific components in concrete, the compatibility problem of polymeric polyol glue reducer and other admixtures is solved, and the effect of improving the flowability and strength of concrete is achieved, which significantly improves crack resistance and durability.
Patent Information
- Application Number
- CN202510036376.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
Polymer polyol glue reducing agents have compatibility problems with other concrete admixtures, which affect the performance and quality of concrete.
An environmentally friendly concrete glue reducing agent is adopted, including methylallyl polyoxyethylene ether, acrylic acid, modified fibers, initiators, modified starch, sodium lignin sulfonate and chain transfer agent. Through the combination of these components, a molecular adsorption layer, a lubricating layer and a mesh structure are formed to improve the flowability, strength and durability of the concrete.
It effectively improves the flowability and strength of concrete, improves tensile strength, wear resistance and impact resistance, significantly improves the crack resistance and durability of concrete, while maintaining the flow characteristics of concrete.
Smart Images

Figure BDA0005235652900000091 
Figure BDA0005235652900000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete building materials, and in particular to an environmentally friendly concrete adhesive reducer and a preparation method thereof. Background Art
[0002] Concrete is a composite material made of water, aggregates (such as sand, stone) and cement in a certain proportion. During the production process of concrete, various admixtures are added to improve its performance. Among them, the gel reducer is a substance added during the preparation of concrete that can improve the performance of concrete.
[0003] Concrete glue reducer, also known as concrete enhancer, can effectively reduce the amount of cementitious materials while maintaining the slump of concrete and the 28-day compressive strength. It has adsorption and dispersion, filling and lubrication, retarding and strengthening effects.
[0004] Commonly used glue reducers include polymer polyol glue reducers, whose main component is a polyol mixture. This type of glue reducer can partially or completely replace triethanolamine and other ingredients in traditional glue reducers, and has the advantages of low cost and good effect.
[0005] There are compatibility issues between polymer polyol-based adhesive reducers and other concrete admixtures (such as water reducers, retarders, etc.). If the compatibility is poor, it may affect the performance and quality of concrete and even cause quality problems in concrete. Summary of the invention
[0006] In order to improve the compatibility problem between polymer polyol-based adhesive reducers and other concrete admixtures, the present application provides an environmentally friendly concrete adhesive reducer and a preparation method thereof.
[0007] The present application provides an environmentally friendly concrete adhesive reducer, which adopts the following technical solution: An environmentally friendly concrete adhesive reducer comprises the following raw materials, measured by weight: 80-100 parts of methyl allyl polyoxyethylene ether, 20-25 parts of acrylic acid, 15-20 parts of modified fiber, 5-8 parts of initiator, 22-26 parts of modified starch, 8-10 parts of sodium lignin sulfonate, 3-5 parts of chain transfer agent and 280-300 parts of deionized water.
[0008] By adopting the above technical solution, the long-chain molecules of methyl allyl polyoxyethylene ether can form a molecular adsorption layer in the water phase of concrete, forming an interface between water and solid phase, which can prevent direct contact between cement, sand, stone and other particles, thereby maintaining relative stability between concrete particles and maintaining its flow characteristics. Acrylic acid reacts with water molecules to form a water-soluble polymer, which can form a lubricating layer in concrete, effectively reducing the friction resistance inside the concrete, thereby improving the fluidity and pumpability of the concrete.
[0009] The surface pores and functional groups of the modified fibers enable the modified fibers to be adsorbed on the surface of methyl allyl polyoxyethylene ether, which can fill the gaps in the concrete and improve the tensile strength, wear resistance and impact resistance of the concrete. Although the modified fibers will reduce the fluidity of the concrete to a certain extent, the addition of the modified fibers can significantly improve the crack resistance and impact resistance of the concrete. The modified fibers form a mesh structure in the concrete, which can effectively absorb and disperse the impact force, thereby improving the durability of the concrete. The initiator initiates the polymerization of monomers to form a high molecular polymer, forming a stable high molecular network structure, and improving the corresponding performance of the concrete. The chain transfer agent can prevent the cross-linking reaction between polymer chains and maintain the fluidity and stability of the gel reducer.
[0010] Modified starch plays a thickening role in the gel reducer, increasing the viscosity of the system, which helps to improve the stability and fluidity of the colloid; modified starch forms a microscopic gel structure in concrete, increases the flexibility and deformation capacity of concrete, improves its crack resistance, improves the fluidity and processing performance of concrete, reduces the mixing time of concrete, and improves its early strength. Sodium lignin sulfonate can interact with cement particles, making cement particles smaller and increasing the friction between cement particles and water, so that the moisture in the concrete can better combine with cement particles, improving the strength and fluidity of the concrete. The combination of the various components in this application not only improves the fluidity of concrete, but also increases the strength and durability of concrete.
[0011] Preferably, the method for preparing the modified fiber comprises the following steps: (1) dispersing polypropylene fibers in a sodium hydroxide solution, stirring for 20-25 minutes, washing with water, and then dispersing them in a dopamine aqueous solution, stirring for 1-2 hours, and drying to obtain pretreated fibers; (2) Dispersing the modified Rongalite in deionized water, adding the pretreated fiber of step (1) and polyglutamic acid, stirring at a temperature of 55-60° C. for 40-45 minutes, and drying to obtain modified fiber.
[0012] By adopting the above technical scheme, the sodium hydroxide solution erodes the surface of the polypropylene fiber to a certain extent, thereby increasing the surface roughness and specific surface area of the polypropylene fiber. The polypropylene fiber is mixed with the dopamine aqueous solution, and the self-polymerization-adhesion characteristics of dopamine are used to modify the polypropylene fiber, which has strong adhesion, so that the modified polypropylene fiber can be tightly attached to the surface of other materials.
[0013] Modified Rongalite has a water-reducing effect, can reduce the viscosity of concrete, improve the fluidity of concrete, pre-treated fiber has good crack resistance, impact resistance and toughness, modified Rongalite can be loaded on the surface of pre-treated fiber, improve the strength and durability of pre-treated fiber, polyglutamic acid has good hygroscopicity and biocompatibility, as a thickener, stabilizer and humectant, it helps the pre-treated fiber and modified Rongalite to adhere tightly, and helps to improve the workability and water retention of concrete later. The water retention effect of polyglutamic acid and the water-reducing effect of modified Rongalite can jointly improve the workability of concrete, making it easier to construct. The reinforcing effect of polypropylene fiber and the water-reducing effect of modified Rongalite can jointly improve the strength and durability of concrete, reduce cracks and improve crack resistance. The modified fiber obtained is subsequently applied to concrete to improve the fluidity, strength and durability of concrete.
[0014] Preferably, the mass ratio of the polypropylene fiber, the modified Rongalite and the polyglutamic acid is 1:0.4-0.5:0.1-0.2.
[0015] By adopting the above technical scheme, the mass ratio of polypropylene fiber, modified Rongalite and polyglutamic acid is further limited within a certain range, and the obtained modified fiber has good comprehensive performance, which is applied to concrete to improve the corresponding performance of concrete. Polypropylene fiber has high elastic modulus, good dispersibility and good chemical stability, modified Rongalite has water-reducing effect, improves the fluidity of concrete, polyglutamic acid has strong hydrophilicity and water retention capacity, polypropylene fiber, modified Rongalite and polyglutamic acid have synergistic effect when mixed, and polyglutamic acid makes polypropylene fiber and modified Rongalite adhere closely, improves the crack resistance, flexural strength and impact toughness of concrete, improves the fluidity, encapsulation and water retention of concrete, and improves the comprehensive performance of concrete.
[0016] Preferably, the preparation method of the modified Rongalite comprises the following steps: grinding and sieving the Rongalite, dispersing the Rongalite in deionized water, stirring for 30-35 minutes, adding graphene and hydroxyethyl cellulose, stirring for 1-2 hours, drying, and grinding to obtain the modified Rongalite.
[0017] By adopting the above technical solution, Rongalite is dispersed in deionized water to form a uniform solution, and graphene and hydroxyethyl cellulose are added. Graphene has high mechanical strength and effectively improves the strength and toughness of the system. Hydroxyethyl cellulose can significantly improve the working performance of concrete, including water retention, viscosity and plasticity, making concrete easier to construct and operate. The π-π interaction force between graphene sheets is strong and agglomeration is prone to occur. The introduction of hydroxyethyl cellulose can effectively hinder the aggregation of graphene sheets, making them stably dispersed in deionized water.
[0018] Rongalite is loaded on the surface of graphene. Hydroxyethyl cellulose increases the adhesion between Rongalite and graphene, making Rongalite stably loaded on the surface of graphene. It is subsequently applied to concrete to fill the structure of concrete, reduce the voids and pores in concrete, and improve the density and strength of concrete. It is combined with raw materials such as methyl allyl polyoxyethylene ether to improve the fluidity of concrete, improve the water reduction effect and enhance the performance of concrete. In addition, graphene can promote the hydration reaction of cement composite materials to be more sufficient and complete, refine the pore structure, and improve the density. Hydroxyethyl cellulose can improve the fluidity of concrete, making it smoother during pumping, pouring and vibrating, and improving construction efficiency.
[0019] Preferably, the mass ratio of the Rongalite, graphene and hydroxyethyl cellulose is 1g:60-70mg:0.2-0.3g.
[0020] By adopting the above technical solution, the mass ratio of Rongalite, graphene and hydroxyethyl cellulose is further limited within a certain range, Rongalite has a filling effect, which reduces the gaps between concrete particles, thereby improving the microstructure of concrete, improving the fluidity of concrete, and helping the concrete to move more smoothly during mixing and pouring. Graphene has high mechanical strength and hydroxyethyl cellulose has viscosity, so that Rongalite is stably loaded on the surface of graphene, and subsequently fills the structure of concrete, improves the density and strength of concrete, and improves the fluidity of concrete.
[0021] Preferably, the method for preparing the modified starch comprises the following steps: (1) dispersing corn starch in deionized water, adjusting the solution pH to 3-4, adding α-amylase, stirring at a temperature of 55-60° C. for 1-1.5 hours, cooling and filtering, and vacuum drying and grinding the filtrate to obtain pretreated starch; (2) Dispersing the modified chestnut shell powder in deionized water, adding the pretreated starch and silane coupling agent of step (1), stirring for 1-2 hours, drying, and grinding to obtain modified starch.
[0022] By adopting the above technical solution, after adding α-amylase, the enzyme will act on the α-1,4-glycosidic bonds on the surface of starch granules, hydrolyze them into small molecules such as oligosaccharides or maltose, destroy the crystalline structure of starch granules, and change the molecular weight distribution and chain length distribution of starch, thereby improving the gelatinization properties, viscosity and stability of starch.
[0023] Cellulose and lignin components in the modified chestnut shell powder can provide additional structural support for the system and enhance the overall strength of the material. Starch can fill the gaps between chestnut shell powder particles and has a certain film-forming property, covering the surface of chestnut shell powder particles. Silane coupling agents can build a "molecular bridge" between chestnut shell powder and starch, tightly connecting two materials with different properties together, and improving the overall performance and bonding strength of the mixed system. Silane coupling agents can also improve the dispersibility of chestnut shell powder in starch solution, prevent particle agglomeration and precipitation, and thus improve the uniformity and stability of the mixed system. Subsequent applications in concrete can fill tiny pores in concrete, improve the density and strength of concrete, increase the fluidity of concrete, and make concrete easier to mix, pour and vibrate.
[0024] Preferably, the mass ratio of the corn starch, the modified chestnut shell powder and the silane coupling agent is 1:0.5-0.6:0.2-0.3.
[0025] By adopting the above technical solution, the mass ratio of corn starch, modified chestnut shell powder and silane coupling agent is further limited within a certain range, and the obtained mixture has good comprehensive performance. Corn starch can increase the fluidity of concrete in concrete, making concrete easier to mix, pour and vibrate. Modified chestnut shell powder fills the tiny pores in concrete and improves the density and strength of concrete. Silane coupling agent can build a "molecular bridge" between chestnut shell powder and starch, tightly connecting two materials with different properties together, and improving the overall performance and bonding strength of the mixed system. After mixing chestnut shell powder, starch and silane coupling agent, a variety of interactions and synergistic effects will occur, from improving the density, strength, durability and waterproof performance of concrete.
[0026] Preferably, the preparation method of the modified chestnut shell powder comprises the following steps: crushing the chestnut shell, sieving, and then dispersing it in deionized water, adding nano titanium dioxide particles and chitosan, stirring at a temperature of 70-75°C for 1-2h, and drying to obtain the modified chestnut shell powder.
[0027] By adopting the above technical scheme, chestnut shell powder particles can fill the tiny pores in concrete, improve the density and strength of concrete, and nano titanium dioxide particles have good adsorption due to their small size effect and surface effect, and can be loaded on the surface of chestnut shell powder particles, improving the mechanical properties, thermal stability and chemical stability of chestnut shell powder particles. Chitosan has a certain viscosity, so that chestnut shell powder particles and nano titanium dioxide particles are tightly bonded, increasing the strength and stability of the mixture. Chestnut shell powder, nano titanium dioxide particles and chitosan work synergistically to improve the density, strength, durability and weathering resistance of concrete. Improve the workability of concrete, improve water retention and adhesion, and the mixed reducer can reduce the amount of cement in a unit of concrete, thereby reducing the cost of concrete.
[0028] Preferably, the mass ratio of the chestnut shell, nano-titanium dioxide particles and chitosan is 1:0.3-0.5:0.1-0.2.
[0029] By adopting the above technical scheme, the mass ratio of chestnut shell, nano titanium dioxide particles and chitosan is further limited within a certain range, and the strength of the mixture is improved. Chestnut shell can fill the tiny pores in concrete, and improve the density and strength of concrete. Nano titanium dioxide particles can fill the voids in concrete and strengthen the internal structure of concrete, thereby improving the hardness and strength of concrete. Chitosan has a certain viscosity, so that chestnut shell powder particles and nano titanium dioxide particles are tightly bonded, increasing the strength and stability of the mixture. The mixture of chestnut shell, nano titanium dioxide particles and chitosan has a synergistic effect, which improves the density, strength, durability and weathering resistance of concrete. Chestnut shell, nano titanium dioxide and chitosan can refine the microstructure of concrete, improve the density and uniformity of concrete, and further improve the performance of concrete.
[0030] In the second aspect, the present application also provides a method for preparing an environmentally friendly concrete glue reducer, comprising the following steps: mixing methyl allyl polyoxyethylene ether, modified starch, and deionized water, adding an initiator at a temperature of 60-65°C, then adding acrylic acid, modified fiber, chain transfer agent, and sodium lignin sulfonate, stirring evenly, adjusting the pH to 6-7, and obtaining an environmentally friendly concrete glue reducer.
[0031] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing environmentally friendly concrete reducer. The obtained environmentally friendly concrete reducer has good mechanical properties and stability.
[0032] In summary, this application has the following beneficial effects: 1. The surface pores and functional groups of the modified fibers in the present application enable the modified fibers to be adsorbed on the surface of methyl allyl polyoxyethylene ether, which can fill the gaps in concrete and improve the tensile strength, wear resistance and impact resistance of concrete. The addition of modified fibers can significantly improve the crack resistance and impact resistance of concrete. The modified fibers form a network structure in the concrete, which can effectively absorb and disperse impact force, thereby improving the durability of the concrete.
[0033] 2. In the present application, the modified starch plays a thickening role in the gel reducer, increases the viscosity of the system, and thus helps to improve the stability and fluidity of the colloid. The modified starch forms a microscopic gel structure in the concrete, increases the flexibility and deformation capacity of the concrete, improves its crack resistance, improves the fluidity and processing performance of the concrete, reduces the mixing time of the concrete, and improves its early strength.
[0034] 3. The long-chain molecules of methyl allyl polyoxyethylene ether in the present application can form a molecular adsorption layer in the water phase of concrete, forming an interface between water and the solid phase. This interface can prevent direct contact between cement, sand, stone and other particles, thereby maintaining relative stability between concrete particles and maintaining its flow characteristics. DETAILED DESCRIPTION
[0035] The present application is further described in detail below with reference to the embodiments.
[0036] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0037] Preparation example of modified fiber Preparation Example 1-1 The preparation method of the modified fiber comprises the following steps: (1) 50 kg of polypropylene fibers were dispersed in 70 L of a 10% sodium hydroxide solution, stirred for 25 min, washed with water, and then dispersed in 80 L of a 5 g / L dopamine aqueous solution, stirred for 2 h, and dried to obtain pretreated fibers; (2) Dispersing the modified Rongalite in 80 L of deionized water, adding the pretreated fiber of step (1) and polyglutamic acid, stirring at 60° C. for 45 min, and drying to obtain modified fiber.
[0038] The mass ratio of polypropylene fiber, modified Rongalite and polyglutamic acid is 1:0.4:0.1.
[0039] The preparation method of modified Rongalite comprises the following steps: grinding 40 kg of Rongalite, passing through a 20-mesh sieve, and then dispersing in 60 L of deionized water, stirring for 35 minutes, adding graphene and hydroxyethyl cellulose, stirring for 2 hours, drying, and grinding to obtain modified Rongalite; wherein the Rongalite is purchased from Jinan 168 Chemical Co., Ltd., and polyglutamic acid is purchased from Guangdong Mingcheng Biotechnology Co., Ltd.
[0040] The mass ratio of Rongalite, graphene and hydroxyethyl cellulose is 1g:60mg:0.3g.
[0041] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified Rongalite is added.
[0042] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (2), polyglutamic acid is not added.
[0043] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of polypropylene fiber, modified Rongalite and polyglutamic acid is 1:0.5:0.2.
[0044] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of polypropylene fiber, modified Rongalite and polyglutamic acid is 1:0.1:0.6.
[0045] Preparation Example 1-6 The difference from Preparation Example 1-1 is that graphene is not added in the preparation method of the modified Rongalite.
[0046] Preparation Example 1-7 The difference from Preparation Example 1-1 is that hydroxyethyl cellulose is not added in the preparation method of the modified Rongalite.
[0047] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of Rongalite, graphene and hydroxyethyl cellulose is 1 g:70 mg:0.2 g.
[0048] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of Rongalite, graphene and hydroxyethyl cellulose is 1 g:40 mg:0.8 g.
[0049] Preparation example of modified starch Preparation Example 2-1 The preparation method of modified starch comprises the following steps: (1) 40 kg of corn starch was dispersed in 60 L of deionized water, the pH of the solution was adjusted to 4, 3 kg of α-amylase was added, the mixture was stirred at 60 ° C for 1.5 h, the temperature was lowered and filtered, and the filtrate was vacuum dried and ground to obtain pretreated starch; (2) Dispersing the modified chestnut shell powder in 90 L of deionized water, adding the pretreated starch and silane coupling agent of step (1), stirring for 2 h, drying, and grinding to obtain modified starch; wherein the silane coupling agent is silane coupling agent KH550.
[0050] The mass ratio of corn starch, modified chestnut shell powder and silane coupling agent is 1:0.5:0.3.
[0051] The preparation method of modified chestnut shell powder comprises the following steps: crushing 50 kg chestnut shells, passing through an 80-mesh sieve, and then dispersing them in 80 L deionized water, adding nano titanium dioxide particles and chitosan, stirring at a temperature of 75° C. for 2 hours, and drying to obtain modified chestnut shell powder.
[0052] The mass ratio of chestnut shell, nano-titanium dioxide particles and chitosan is 1:0.3:0.2.
[0053] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modified chestnut shell powder is added.
[0054] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no silane coupling agent is added.
[0055] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of corn starch, modified chestnut shell powder and silane coupling agent is 1:0.6:0.2.
[0056] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of corn starch, modified chestnut shell powder and silane coupling agent is 1:0.1:0.7.
[0057] Preparation Example 2-6 The difference from Preparation Example 2-1 is that in the preparation method of the modified chestnut shell powder, no nano titanium dioxide particles are added.
[0058] Preparation Example 2-7 The difference from Preparation Example 2-1 is that chitosan is not added in the preparation method of the modified chestnut shell powder.
[0059] Preparation Example 2-7 The difference from Preparation Example 2-1 is that the mass ratio of chestnut shell, nano-titanium dioxide particles and chitosan is 1:0.5:0.1.
[0060] Preparation Example 2-8 The difference from Preparation Example 2-1 is that the mass ratio of chestnut shell, nano-titanium dioxide particles and chitosan is 1:0.05:0.5. Example
[0061] Example 1 An environmentally friendly concrete adhesive reducer comprises the following raw materials by weight: 80 kg of methyl allyl polyoxyethylene ether, 20 kg of acrylic acid, 15 kg of modified fiber, 5 kg of initiator, 22 kg of modified starch, 8 kg of sodium lignin sulfonate, 3 kg of chain transfer agent and 280 kg of deionized water.
[0062] The preparation method of the above-mentioned environmentally friendly concrete glue reducer comprises the following steps: mixing methyl allyl polyoxyethylene ether, modified starch and deionized water, adding an initiator at a temperature of 60°C, then adding acrylic acid, modified fiber, chain transfer agent and sodium lignin sulfonate, stirring evenly, adjusting pH to 7, and obtaining an environmentally friendly concrete glue reducer.
[0063] The initiator was vitamin C, the chain transfer agent was sodium hypophosphite, and methyl allyl polyoxyethylene ether was purchased from Wuhan Jixin Yibang Biotechnology Co., Ltd.
[0064] The modified fiber was prepared by using Preparation Example 1-1; and the modified starch was prepared by using Preparation Example 2-1.
[0065] Example 2 An environmentally friendly concrete adhesive reducer, which differs from Example 1 in that, by weight, it includes the following raw materials: 100 kg of methyl allyl polyoxyethylene ether, 25 kg of acrylic acid, 20 kg of modified fiber, 8 kg of initiator, 26 kg of modified starch, 10 kg of sodium lignin sulfonate, 5 kg of chain transfer agent, and 300 kg of deionized water.
[0066] Example 3 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Example 1-2.
[0067] Example 4 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-3.
[0068] Example 5 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-4.
[0069] Example 6 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-5.
[0070] Example 7 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-6.
[0071] Example 8 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-7.
[0072] Example 9 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-8.
[0073] Example 10 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-9.
[0074] Embodiment 11 An environmentally friendly concrete adhesive reducer, which is different from Example 1 in that the modified starch is prepared using Preparation Example 2-2.
[0075] Example 12 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified starch is prepared using Preparation Example 2-3.
[0076] Embodiment 13 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified starch is prepared using Preparation Examples 2-4.
[0077] Embodiment 14 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified starch is prepared using Preparation Examples 2-5.
[0078] Embodiment 15 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified starch is prepared using Preparation Examples 2-6.
[0079] Example 16 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified starch is prepared using Preparation Examples 2-7.
[0080] Embodiment 17 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified starch is prepared using Preparation Example 2-8.
[0081] Embodiment 18 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified starch is prepared using Preparation Example 2-9.
[0082] Comparative Example Comparative Example 1 An environmentally friendly concrete adhesive reducer, which differs from Example 1 in that no modified fiber is added.
[0083] Comparative Example 2 An environmentally friendly concrete adhesive reducer is different from Example 1 in that the modified fiber is replaced by an equal amount of fiber.
[0084] Comparative Example 3 An environmentally friendly concrete adhesive reducer, which differs from Example 1 in that modified starch is not added.
[0085] Comparative Example 4 An environmentally friendly concrete adhesive reducer, which differs from Example 1 in that the modified starch is replaced by an equal amount of starch.
[0086] Performance testing The environmentally friendly concrete adhesive reducers prepared in Examples 1-18 and Comparative Examples 1-4 were subjected to performance tests. The test was carried out according to JCT 2469-2018 standard, with a design strength of C30 and using Conch (PO42.5 grade) cement 300kg / m 3 , gravel 10-15mm continuous grading, sand ratio 30%, water consumption is based on the water consumption when the slump of the benchmark concrete is 100±10mm, the amount of glue reducing agent is 0.7%, and the test results are shown in Table 1.
[0087] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the concrete glue reducer prepared in Examples 1-2 of the present application has good mechanical properties, glue reduction rate and mechanical strength. Among them, the 7d compressive strength of Example 1 reaches 32.5MPa, the 28d compressive strength reaches 45.3MPa, the slump out of the machine is 115mm, the strength loss rate after 50 freeze-thaw cycles is 56%, and the glue reduction rate is 10.5%, indicating that the prepared environmentally friendly concrete glue reducer has good mechanical properties and mechanical strength, and the various components cooperate with each other, which not only improves the fluidity of the concrete, but also increases the strength and durability of the concrete.
[0088] In the preparation method of the modified fiber of Examples 3-4, modified Rongalite and polyglutamic acid are not added respectively, and the mass ratio of polypropylene fiber, modified Rongalite and polyglutamic acid is changed in Examples 5-6. As can be seen from Table 1, the test results of the 7d and 28d compressive strength, machine slump, 50 freeze-thaw cycle strength loss rate and rubber reduction rate of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the corresponding performance test of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1 and 5, indicating that the polypropylene fiber has high elastic modulus, good dispersibility and good chemical stability, the modified Rongalite has a water-reducing effect, the polyglutamic acid has a strong hydrophilicity and water retention capacity, the polypropylene fiber, the modified Rongalite and the polyglutamic acid have a synergistic effect, and the polyglutamic acid makes the polypropylene fiber and the modified Rongalite adhere closely, improves the crack resistance, flexural strength and impact toughness of the concrete, improves the fluidity, encapsulation and water retention of the concrete, and improves the comprehensive performance of the concrete.
[0089] In the preparation method of modified Rongalite in Examples 7-8, graphene and hydroxyethyl cellulose are not added respectively, and the mass ratio of Rongalite, graphene and hydroxyethyl cellulose is changed in Examples 9-10. As can be seen from Table 1, the test results of 7d and 28d compressive strength, machine slump, 50 freeze-thaw cycle strength loss rate and glue reduction rate of Examples 7-8 are significantly better than those of Example 3, but worse than those of Examples 1-2, while the corresponding performance test of Example 8 is better than that of Examples 7-8, but worse than that of Examples 1 and 9, indicating that graphene has high mechanical strength and hydroxyethyl cellulose has viscosity, so that Rongalite is stably loaded on the surface of graphene, and the structure of the subsequent filling concrete is improved, the density and strength of the concrete are improved, and the fluidity of the concrete is improved.
[0090] In the preparation methods of modified starch in Examples 11-12, modified chestnut shell powder and silane coupling agent are not added respectively, and the mass ratio of corn starch, modified chestnut shell powder and silane coupling agent is changed in Examples 13-14. It can be seen from Table 1 that the test results of 7d and 28d compressive strength, machine slump, 50 freeze-thaw cycle strength loss rate and gel reduction rate of Examples 11-12 are significantly worse than those of Examples 1-2 and Example 13, while the corresponding performance test of Example 14 is better than that of Examples 11-12, but worse than that of Examples 1 and 13, indicating that chestnut shell powder, starch and silane coupling agent will produce a variety of interactions and synergistic effects after mixing, thereby improving the density, strength, durability and waterproof performance of concrete.
[0091] In the preparation method of modified chestnut shell powder in Examples 15-16, nano titanium dioxide particles and chitosan are not added respectively, and the mass ratio of chestnut shell, nano titanium dioxide particles and chitosan is changed in Examples 17-18. As can be seen from Table 1, the test results of 7d and 28d compressive strength, machine slump, 50 freeze-thaw cycle strength loss rate and glue reduction rate of Examples 15-16 are significantly better than those of Example 11, but worse than those of Examples 1-2 and Example 17, and the corresponding performance test of Example 18 is better than that of Examples 15-16, but worse than that of Examples 1 and Example 17, indicating that the mixture of chestnut shell, nano titanium dioxide particles and chitosan has a synergistic effect, which improves the density, strength, durability and weathering resistance of concrete. Chestnut shell, nano titanium dioxide and chitosan can refine the microstructure of concrete, improve the density and uniformity of concrete, and thus further improve the performance of concrete.
[0092] Comparative Examples 1 and 3 do not add modified fiber and modified starch, respectively. As can be seen from Table 1, the test results of 7d and 28d compressive strength, machine slump, 50 freeze-thaw cycle strength loss rate and gel reduction rate of Comparative Examples 1 and 3 are significantly worse than those of Examples 1-2, indicating that the surface pores and functional groups of the modified fiber can make the modified fiber adsorb on the surface of methyl allyl polyoxyethylene ether, fill the gaps in the concrete, and improve the tensile strength, wear resistance and impact resistance of the concrete. The modified starch plays a thickening role in the gel reducer, increases the viscosity of the system, and thus helps to improve the stability and fluidity of the colloid.
[0093] In Comparative Examples 2 and 4, the modified fiber is replaced by an equal amount of fiber, and the modified starch is replaced by an equal amount of starch. As can be seen from Table 1, the test results of the 7d and 28d compressive strength, machine slump, 50 freeze-thaw cycle strength loss rate and gel reduction rate of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than Comparative Examples 1 and 3, indicating that the modified fiber and modified starch of the present application have good mechanical properties, thereby improving the mechanical properties of concrete and maintaining the structural strength and stability of concrete.
[0094] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An environmentally friendly concrete adhesive reducer, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of methyl allyl polyoxyethylene ether, 20-25 parts of acrylic acid, 15-20 parts of modified fiber, 5-8 parts of initiator, 22-26 parts of modified starch, 8-10 parts of sodium lignin sulfonate, 3-5 parts of chain transfer agent and 280-300 parts of deionized water.
2. The environmentally friendly concrete adhesive reducer according to claim 1, characterized in that: The method for preparing the modified fiber comprises the following steps: (1) dispersing polypropylene fibers in a sodium hydroxide solution, stirring for 20-25 minutes, washing with water, and then dispersing them in a dopamine aqueous solution, stirring for 1-2 hours, and drying to obtain pretreated fibers; (2) Dispersing the modified Rongalite in deionized water, adding the pretreated fiber and polyglutamic acid in step (1), stirring at a temperature of 55-60° C. for 40-45 minutes, and drying to obtain modified fiber.
3. The environmentally friendly concrete adhesive reducer according to claim 2, characterized in that: The mass ratio of the polypropylene fiber, modified Rongalite and polyglutamic acid is 1:0.4-0.5:0.1-0.
2.
4. The environmentally friendly concrete adhesive reducer according to claim 2, characterized in that: The preparation method of the modified Rongalite comprises the following steps: grinding and sieving the Rongalite, dispersing the Rongalite in deionized water, stirring for 30-35 minutes, adding graphene and hydroxyethyl cellulose, stirring for 1-2 hours, drying, and grinding to obtain the modified Rongalite.
5. The environmentally friendly concrete adhesive reducer according to claim 4, characterized in that: The mass ratio of the Rongalite, graphene and hydroxyethyl cellulose is 1g:60-70mg:0.2-0.3g.
6. The environmentally friendly concrete adhesive reducer according to claim 1, characterized in that: The preparation method of the modified starch comprises the following steps: (1) Dispersing corn starch in deionized water, adjusting the solution pH to 3-4, adding α-amylase, stirring at a temperature of 55-60°C for 1-1.5 hours, cooling and filtering, vacuum drying and grinding the filtrate to obtain pretreated starch; (2) Dispersing the modified chestnut shell powder in deionized water, adding the pretreated starch and silane coupling agent of step (1), stirring for 1-2 hours, drying, and grinding to obtain modified starch.
7. The environmentally friendly concrete adhesive reducer according to claim 6, characterized in that: The mass ratio of the corn starch, the modified chestnut shell powder and the silane coupling agent is 1:0.5-0.6:0.2-0.
3.
8. The environmentally friendly concrete adhesive reducer according to claim 6, characterized in that: The preparation method of the modified chestnut shell powder comprises the following steps: crushing chestnut shells, sieving, and then dispersing them in deionized water, adding nano titanium dioxide particles and chitosan, stirring at a temperature of 70-75° C. for 1-2 hours, and drying to obtain the modified chestnut shell powder.
9. The environmentally friendly concrete adhesive reducer according to claim 8, characterized in that: The mass ratio of the chestnut shell, the nano titanium dioxide particles and the chitosan is 1:0.3-0.5:0.1-0.
2.
10. The method for preparing an environmentally friendly concrete adhesive reducer according to claim 1, characterized in that: The method comprises the following steps: mixing methyl allyl polyoxyethylene ether, modified starch and deionized water, adding an initiator at a temperature of 60-65°C, adding acrylic acid, modified fiber, a chain transfer agent and sodium lignin sulfonate, stirring evenly, adjusting the pH to 6-7, and obtaining an environmentally friendly concrete glue reducer.